EIF4G is retained on ribosomes elongating and terminating on short upstream ORFs to control reinitiation in yeast. Issue 15 (5th August 2021) - Mohammad, Mahabub Pasha; Smirnova, Anna; Gunišová, Stanislava; Valášek, Leoš Shivaya
Abstract: Translation reinitiation is a gene-specific translational control mechanism. It is characterized by the ability of short upstream ORFs to prevent full ribosomal recycling and allow the post-termination 40S subunit to resume traversing downstream for the next initiation event. It is well known that variable transcript-specific features of various uORFs and their prospective interactions with initiation factors lend them an unequivocal regulatory potential. Here, we investigated the proposed role of the major initiation scaffold protein eIF4G in reinitiation and its prospective interactions with uORF's cis -acting features in yeast. In analogy to the eIF3 complex, we found that eIF4G and eIF4A but not eIF4E (all constituting the eIF4F complex) are preferentially retained on ribosomes elongating and terminating on reinitiation-permissive uORFs. The loss of the eIF4G contact with eIF4A specifically increased this retention and, as a result, increased the efficiency of reinitiation on downstream initiation codons. Combining the eIF4A-binding mutation with that affecting the integrity of the eIF4G1–RNA2-binding domain eliminated this specificity and produced epistatic interaction with a mutation in one specific cis -acting feature. We conclude that similar to humans, eIF4G is retained on ribosomes elongating uORFs to control reinitiation also in yeast.